If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10(X + -1) = -20 Reorder the terms: -10(-1 + X) = -20 (-1 * -10 + X * -10) = -20 (10 + -10X) = -20 Solving 10 + -10X = -20 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -10X = -20 + -10 Combine like terms: 10 + -10 = 0 0 + -10X = -20 + -10 -10X = -20 + -10 Combine like terms: -20 + -10 = -30 -10X = -30 Divide each side by '-10'. X = 3 Simplifying X = 3
| h=2+-6g | | 5(3+4x)=2(10x+8)-1 | | -7+-4+-3= | | -2(X-1)+7=15 | | 12+-11= | | 5-3(X+2)=-1 | | 3(2+4x)=4(3x+5) | | 6m-3=12 | | -5+7=2 | | 4(5+2x)=3x+55 | | 8x+3y=59 | | 4r^2-r=5 | | 6-2h=h+18g | | c(4+5d)=9d-7 | | 4[x+4(5-x)]=2x+1 | | 2x=100x-10x | | 3(x-2)=6-(x+8) | | 4x^2+3xy+8x+6y=0 | | 2x=100z-10y | | 6x-7=5x-1 | | 3(3m+7)-2(m+9)= | | Y=2.842105263 | | 2(3y-9)-4(y-6)= | | y-10=2x | | 9(y-6)=-10y | | b^2+7b-18=0 | | 8m-1=7m-3 | | 3.5(x-2)+3.2x= | | x+x+x=100 | | x+x=x-10+100 | | -20=6y | | 1y=12 |